REVEALING GREEN CAMPAIGN CONCEPT ON PUBLIC RELATIONS PERSPECTIVE: A SYSTEMATIC LITERATURE REVIEW - Hasna, Sofia; Patrianti, Tria; Iftatunnisa, Putri Vania (Perspektif Komunikasi: Jurnal Ilmu Komunikasi Politik dan Komunikasi Bisnis, 2024)
Green campaign activities are a concept currently utilized by communication practitioners in both profit and nonprofit organizations to emphasize the importance of sustainable environmental practices amid climate and environmental crises. This green campaign aligns with the Sustainable Development Goals (SDGs), specifically Pillar 6, which focuses on environmental development. Additionally, this concept is closely related to public relations (PR) activities, including research, planning, execution, and evaluation. Therefore, this study aims to examine the concept of green campaigns from a public relations perspective to understand how it functions within this field. This research employs a qualitative descriptive method through a systematic literature review (SLR), analyzing data from 100 articles obtained from Google Scholar. The findings indicate that research on the green campaign concept in public relations gained popularity between 2016 and 2018. The green campaign is strongly linked to public relations as a persuasive campaign concept that promotes environmentally sustainable innovations. Furthermore, from a public relations perspective, the green campaign emphasizes outcomes that create environmental value and raise public awareness of environmental issues. Expected applications of the green campaign include green trust (public trust in environmental issues) and green consumer behavior (shifting societal behavior toward more sustainable and eco-friendly living). The green campaign concept is also associated with green marketing campaigns and marketing communication, as they all influence consumer behavior. The presence of the green campaign concept in modern communication activities is marked by increasing public awareness of environmental issues. Therefore, in the context of public relations, the green campaign serves as part of a communication strategy that intersects with environmental issues.